THE STUDY OF PERFORMANCE AND DIAGNOSTIC EFFICACY OF WIDAL TEST AND STOOL CULTURE IN THE DIAGNOSIS OF TYPHOID FEVER AMONG SUSPECTED PATIENTS IN LOW INCOME COUNTRIES : A COMPREHENSIVE SYSTEMATIC REVIEW - Pambajeng, Cesil Raras; Siskanondang Manalu, Ema Febianti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Typhoid fever is a significant health challenge in low- and middle-income countries (LMIC) due to inadequate access to clean water and sanitation infrastructure. The prevalence of typhoid fever, as determined by the Widal test, has quadrupled between 2014 and 2018, with sub-Saharan Africa having the highest infection load. Inadequate diagnosis and treatment are crucial to prevent complications. Rapid serological tests, lack of standard laboratory practices, and limited disease surveillance systems contribute to the uncertainty in disease burden. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. The literature was assembled using a variety of online databases, including ScienceDirect, PubMed, and SagePub. Result: Utilizing reliable resources including Science Direct, SagePub, and PubMed, the study examined around 800 papers. After seven pieces were determined to be relevant for methodical investigation, a more thorough examination of the complete material was conducted. Conclusion: Diagnostics for typhoid fever, a common illness in low- and middle-income countries, mostly depend on the Widal test. On the other hand, variables such as malaria parasitemia, antigen standardization, and patient population affect how accurate the test is. The suggested diagnostic strategy identifies Salmonella from blood, stool, and bone marrow cultures; this calls for significant upgrades to laboratory resources as well as continuous training.